Applications of innovative configurations of double absorption heat transformers in water purification technology - Khamooshi, Mehrdad; Parham, Kiyan; Roozbeh, Iman; Ensafisoroor, Hamed (Desalination Publ, 2016)
In this study, first law of thermodynamics has been employed to analyze the performances of two different configurations of double absorption heat transformers (DAHTs) in water purification system. The upgraded heat in the absorber of the absorption heat transformers provides the heat for desalination process. The first investigated configuration is the most efficient DAHT according to the literature, and the second one is a novel configuration proposed by the authors. The aim of this research was to investigate the effects of different parameters on the studied configurations of DAHTs and the desalination system and to compare their performances in detail. Additionally by considering the quantity of the produced water, both the configurations were optimized. The results revealed that the proposed configuration is capable of producing freshwater for 806 residual units.
Keywords: Desalination; COP; LiBr + H2O; Crystallization risk; Double; Absorption heat transformer